PROBLEMATIKA PENDIDIKAN AGAMA ISLAM DI ERA DIGITAL: ANALISIS DARI PERSPEKTIF IDEOLOGIS DAN INSTITUSIONAL - Oktavia, Nur Afni; Najmi, Lailan; Fadriati, Fadriati; Suryana, Ermis (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2025)
The rapid development of digital technology has brought significant transformations to various aspects of human life, including the implementation of Islamic Religious Education (PAI). Nevertheless, the implementation of PAI in the digital era encounters a range of complex challenges, both ideologically and institutionally. This study aims to critically examine the dynamics and challenges of PAI implementation within the context of educational digitalization, with particular attention to how religious ideology and institutional policies shape the direction and quality of religious instruction in educational institutions. The research adopts a library-based methodology with a qualitative analytical approach, drawing on a variety of primary and secondary sources, including peer-reviewed academic journals, scholarly books, and national education policy documents. The findings reveal that digitalization offers substantial opportunities to enhance access and foster innovation in PAI learning; however, it simultaneously generates ideological concerns in the form of fragmented religious understanding, as well as institutional challenges related to regulatory frameworks, educators’ digital competencies, and the authenticity of digital instructional resources. The study concludes by emphasizing the urgent need for a reconstruction of PAI paradigms and policies that prioritize religious moderation, strengthen digital literacy, and integrate spiritual values with technological advancement, ensuring that Islamic religious education remains relevant and meaningful in the digital era.